2017
DOI: 10.22146/ijg.17601
|View full text |Cite
|
Sign up to set email alerts
|

Application of Geographically Weighted Regression for Vulnerable Area Mapping of Leptospirosis in Bantul District

Abstract: Geographically Weighted Regression (GWR) is regression model that developed for data modeling with continuous respond variable and considering the spatial or location aspect. Leptospirosis case happened in some regions in Indonesia, including in Bantul District, Special Region of Yogyakarta. The purpose of this study are to determine local and global variable in making vulnerable area model of Leptospirosis disease, determine the best type of weighting function and make vulnerable area map of Leptospirosis. Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 0 publications
2
9
0
1
Order By: Relevance
“…The Akaike Information Criterion (AICc) value, which assesses the relative quality of models given trade-offs between model fit and model complexity [15], showed that the model with temperature seasonality (TS) was more efficient (AIC: 31743.42) in explaining the geographical distribution of leptospirosis transmission risk. This result corroborates findings from other studies showing that geographically weighted regression can offer improvements and additional insights over standard non-spatial regression models for eco-epidemiological studies of leptospirosis [13,15,16,17,18].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The Akaike Information Criterion (AICc) value, which assesses the relative quality of models given trade-offs between model fit and model complexity [15], showed that the model with temperature seasonality (TS) was more efficient (AIC: 31743.42) in explaining the geographical distribution of leptospirosis transmission risk. This result corroborates findings from other studies showing that geographically weighted regression can offer improvements and additional insights over standard non-spatial regression models for eco-epidemiological studies of leptospirosis [13,15,16,17,18].…”
Section: Discussionsupporting
confidence: 90%
“…This, in turn, has fostered the utilization of GIS analytics and geospatial statistics for environmental analyses of infectious diseases [14]. Previous studies have adopted GIS analysis tools in the study of ecological models to explore and analyse spatial variations in relationships between local environmental factors and the occurrences of leptospirosis [13,15,16,17,18].…”
Section: Introductionmentioning
confidence: 99%
“…The Akaike Information Criterion (AICc) value, which assesses the relative quality of models given trade-offs between model fit and model complexity [15], showed that the model with temperature seasonality (TS) was more efficient (AIC: 31743.42) in explaining the geographical distribution of leptospirosis transmission risk. This result corroborates findings from other studies showing that geographically weighted regression can offer improvements and additional insights over standard non-spatial regression models for eco-epidemiological studies of leptospirosis 21 [13,15,16,17,18].…”
Section: Discussionsupporting
confidence: 90%
“…While A is vegetation cover score, B annual precipitation score, C land degradation score and D harvest failure score. Then, food endurance level will be calculated by following formula [9]:…”
Section: Fig 4 Graphical Representation Of Land Degardationmentioning
confidence: 99%
“…2). Then mean annual precipetation value were assigned weightage according to Table 3 [8,9]. Soil map: We get soil map from GWSP (Digital Water Atlas http://atlas.gwsp.org/index.php) with 0.5 degree.…”
Section: Introductionmentioning
confidence: 99%